Structural performance of square recycled aggregate concrete-filled steel tube stub columns under combined loading - Yeo, Alex Ming Yen (Nanyang Technological University, 2021)
This report presents an experimental investigation on the structural behaviour of square recycled aggregate concrete filled-stainless steel tube (RACFSST) stub columns under combined compression and bending. A total of twelve square RACFSST stub column specimens fabricated from two stainless steel square hollow section (SHS) tubes and three types of concrete with recycled aggregate replacement ratios of 0%, 35%, 70% were adopted in the tests. Material tests were also conducted to obtain the material properties of recycled aggregate concretes and stainless-steel tubes. The combined loading test setup, procedures, and observations, including the load–mid-height lateral deflection curves, failure loads and failure modes, were fully reported. The effects of cross-section size and recycled aggregate replacement ratio on the load-carrying capacities of RACFSST stub column specimens were examined, followed by the discussion on the development and distribution of strains. Three current design codes were used to assess the square RACFSST stub columns under combined compression and bending. The result concluded that the European code and Australian standard have demonstrated great level of consistency and accuracy of failure load prediction accuracy while American specification demonstrated conservative failure load predictions with high degree of scattered points. The European code displayed the most accurate failure load predictions among the three design codes.